Minimum separation between lightning protection system and non-integrated metallic structures - Fallah S.N.; Gomes C.; Izadi M.; Kadir M.Z.A.A.; Ahmed R.J.; Jasni J.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Lightning protection; Metals; Roofs; Air-termination systems; constant area criterion; Direct lightning strikes; Electronic systems; Lightning protection systems; Metallic component; Metallic structures; Separation distances; Lightning